Validation of Bahasa Malaysia Version of Psychological Mindedness in a University Population - M.K., Mohd Amiruddin; T.P, Nicholas Pang; D.S, Wendy; Wen L.T, Mathias; Abbylen M., Ervina; Yeoh, Yin Xin (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Psychological mindedness concept is widely accepted to be significantly correlated to psychological strength and mental health. There are multiple scales that attempted to measure psychological mindedness objectively, with the most recent one being Balanced Index of Psychological Mindedness (BIPM). Psychological mindedness is an area of interest in psychiatry and psychology in Malaysia. Hence, this study aims to validate the Bahasa Malaysia Version of Balanced Index of Psychological Mindedness (BIPM-M). MATERIALS AND METHODS: The 14-items scale was translated according to World Health Organization guidelines. 141 participants were recruited from the university population. Participants were required to fill the basic demographic information, as well as Bahasa Malaysia version of Balanced Index of Psychological Mindedness, and two other scales, namely Mindful Awareness Attention Scale (MAAS), and Acceptance and Action Questionnaire-II Scale (AAQ-II). RESULTS: BIPM-M showed excellent internal consistency with Cronbach α of 0.87. As per the original BIPM, the Bahasa Malaysia version also suggested two factor structures in this scale. BIPM-M was significantly correlated with AAQ-II. Conclusion: BIPM-M is a psychometrically sound instrument that can be utilized to assess the psychological mindedness among Malaysians, and certainly enhance the array of psychological assessments available as Malaysia faces the mental health after-effect of COVID-19.